THE SYSTEM OF EDUCATION OF PRESCHOOL EDUCATIONAL INSTITUTIONS IN HIGHER EDUCATION REFORM AS A FACTOR OF PROGRESS - Aliyeva Moxichexra Hasanovna, (Лучшие интеллектуальные исследования, 2023)
Annotation. Students of the direction of preschool education in higher education are told about further improvement of the pre-school education system, ensuring the correct implementation of the educational process of the harmonious generation by educators, as well as effective organization of the process of their professional development.